Internacionalização da Educação Superior no Brasil: políticas em dimensão nacional - Nogueira, Joyce Mesquita (2018)
This dissertation has, as its object of study, the internationalization of Higher Education in Brazil, with a focus on nation-wide policies. The research aimed to analyze the policies - in place at a national scale - for the internationalization of Higher Education in Brazil, aiming also to contribute to widening the comprehension of this component. Moreover, it aimed to assess the implementation processes of such policies, in both the governmental and institutional domains. The methodology is characterized by an approach of qualitative nature, and by the use of procedures identified in the bibliographic research and in the documentary analysis. Such methodological course made it possible to gather data that, subjected to the analysis process, backed the whole study's execution. The theoretical framework had, as its main concepts, the internationalization itself, as well as policies, programs and curricular parameters intended for Higher Education. Such framework relies on authors such as Jane Knight, Marília Morosini, Milton Santos, Marcos Masetto, Enrique Dussel e Zygmunt Bauman. Among the results, it was possible to identify an assortment of various governmental programs for the internationalization of Higher Education, especially for post-graduate studies. However, it was also possible to point out the lack of a single, centralized normative framework to guide this process, as well as the lack of clear and uniform parameters for it. The legitimacy that the internationalization conquered among the scientific community of the very Higher Education institutions highlights how important it is to create mechanisms of assessment, centralized by funding agencies, as is the increase in funding to programs and courses according to their evaluation. The conclusion of investigations, when analyzing nation-wide policies and programs of internationalization of the Higher Education in Brazil, allows to underline that this research's intention was not to draw one single conclusion, but to broaden reflections about the whole process. This resulted in the possibility of identifying challenges and potentialities that encourage continuous construction of new knowledge, in a view that proposes new achievements in the governmental and institutional spheres